Chemical weapons of a termite host and its significance to its inquiline - Costa, Antônio Cláudio Ferreira da (2017)
The chemical defense is an important resource for termites deal with the conflictual interactions to which they are exposed, such as predator-prey, parasite-host and competition for food and shelter. There is a vast array of poisonous substances produced by the frontal gland of termite soldiers, which is the main exocrine gland responsible for defensive secretions of the phylogenetically derived Rhinotermitidae, Serritermitidae and Termitidae. In termite enemies these defensive secretions act as irritants, topical poisons, antihealing greases, immobilizer glues, repellents, unpalatability agents and inhibitors of fungal and bacterial grouwth. Even though, such impressive weaponry is circumvented by Inquilinitermes microcerus Silvestri, 1901 (Termitidae [Termitinae]), an obligatory inquiline of the nest of Constrictotermes cyphergaster (Silvestri, 1901) (Termitidae [Nasutitermitinae]). The present work demonstrated that the frontal gland extract of C. cyphergaster causes no toxic or repelent effect on I. microcerus. These results suggest that I. microcerus has a detoxication mechanism comparable to that employed by C. cyphergaster conspecifics to avoid the toxic consequences of the defensive secretion from their own soldiers. This is the first record of the occurrence of detoxication in an obligatory inquiline against the defensive sectretion of its host.